(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This study aimed to determine the rates of risk factors, diabetes, and glucose intolerance among high-risk subjects for management and treatment. Methods: The study enrolled 1333 eligible subjects aged 30 to 64. Results: The prevalence of subjects with only one risk factor was low at 8.9%, whereas those with two, three, and four or more risk factors were 22.9%, 29.9%, and 37.4%, respectively. Among the risk factors, BMI ≥ 23 was the most common, followed by high blood pressure, physical inactivity, and a family history of diabetes. The prevalence of diabetes and impaired glucose tolerance increased with age. The overall rates of diabetes and impaired glucose tolerance among subjects with risk factors were 10.5% and 13.8%, respectively. The prevalence of diabetes and impaired glucose tolerance gradually increased in subjects with high-risk factors and in the elderly population. Conclusion: The prevalence of diabetes in high-risk subjects between the ages of 30 to 64 is 10.5%, and the prevalence of pre-diabetes and diabetes increases with age. High-risk groups with many risk factors have a high prevalence of diabetes and impaired glucose tolerance.